Penggunaan Pupuk Organik Cair Sebagai Media Produksi Inokulan Azotobacter Chroococcum - Reginawanti Hindersah; H Yulina; Ane Nurbaity (Agrologia, 2013)
Azotobacter chroococcum based biofertilizers have been widely used in the production of environmentally agriculture. For commercial scale, cheap growth media for Azotobcter inoculant  will affect the quality and price of liquid biofertilizer. Growth medium should support cell proliferation as well as its  nitrogen fixation and phytohormone production.  The objective of this study was to determine whether  liquid organic fertilizer (LOF) containing low N can be used as a medium for scaling up  A. chroococcum inoculant without lowering the survival of bacteria and its activity in N2 fixation and phytohormones production. LOF generally contains a complete nutrient although in a small quantities. Experiment was set up in completely randomized design which tested two types of commercial LOF. The results showed that both of  LOF were only able to support cell growth up to 72 hours and at 96 hours cell viability began to decline compared to the control medium,  free-N Ashby. At 72 hour total N and cytokinin  concentration in LOF was lower than those in Ashby media. This study revealed  that LOF  could be used as A. chroococcum growth media, but without optimization of its composition, cell density and cytokinin content would be lower than those of inoculant  in Ashby Media.